1999
DOI: 10.1083/jcb.144.2.305
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTP-binding Protein Rho Regulates Cortical Activities in Cultured Cells during Division

Abstract: We have investigated the role of the small GTP-binding protein Rho in cytokinesis by microinjecting an inhibitor, C3 ribosyltransferase, into cultured cells. Microinjection of C3 into prometaphase or metaphase normal rat kidney epithelial cells induced immediate and global cortical movement of actin toward the metaphase plate, without an apparent effect on the mitotic spindle. During anaphase, concentrated cortical actin filaments migrated with separating chromosomes, leaving no apparent concentration of actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 47 publications
10
101
0
Order By: Relevance
“…However, in fluorescence resonance energy transfer (FRET)-based analysis, it has been concluded that Rho activation is not required for contractile ring formation (Yoshizaki et al, 2003). Others reported that Rho is required for cytokinesis in later stages, such as constriction of the contractile ring or severing of the midbody (Drechsel et al, 1997;O'Connell et al, 1999). In this study, we show that Rho acts as a microtubuledependent signal that specifies the position of the contractile ring.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, in fluorescence resonance energy transfer (FRET)-based analysis, it has been concluded that Rho activation is not required for contractile ring formation (Yoshizaki et al, 2003). Others reported that Rho is required for cytokinesis in later stages, such as constriction of the contractile ring or severing of the midbody (Drechsel et al, 1997;O'Connell et al, 1999). In this study, we show that Rho acts as a microtubuledependent signal that specifies the position of the contractile ring.…”
Section: Introductionmentioning
confidence: 62%
“…It is reported that C3-microinjected HeLa cells frequently detach from the dish or fail to initiate anaphase (O'Connell et al, 1999). To avoid these problems, we used the scrape-loading method to deliver C3 to HeLa cells (McNeil et al, 1984).…”
Section: Translocation Of Active Rho Subfamily Proteins To the Equatomentioning
confidence: 99%
“…Clearly, focusing is not absolutely essential for cytokinesis in situations where either myosin-2 or Rho is inhibited. (71,72) However, when cytokinesis is monitored in living epithelial cells or epithelia in situ, until the terminal phase of the process, the cytokinetic apparatus is tightly focused, cutting through the cell like a knife. Moreover, broad cytokinetic arrays are associated with inefficient furrowing, (20) implying that focusing is important.…”
Section: Contributions Of the Zones To Contractile Arraysmentioning
confidence: 99%
“…O'Connell et al (1999) microinjected C3 ribosyltransferase into mitotic cultured cells to inactivate endogenous Rho, small G proteins which had been implicated in cytokinesis of animal egg cells (Kishi et al, 1993;Mabuchi et al, 1993;Drechel et al, 1996). This treatment enhanced the cortical activities, in that the furrows became wider and ectopic furrows were often formed outside the equatorial region, even when the mitotic spindle was destroyed by nocodazole.…”
Section: Attachment-assisted Mitotic Cleavage (Cytokinesis B)mentioning
confidence: 99%